THE EFFECT OF FINANCING TO DEPOSIT RATIO (FDR), OPERATING EXPENSES TO OPERATING INCOME, AND THIRD-PARTY FUNDS ON THE MARKET SHARE OF SHARIA COMMERCIAL BANKS FOR THE PERIOD 2019-2024 - Rika Nofitasari; Rahmawati Khoiriyah (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
The period 2019-2024 represents a critical phase for the development of Islamic banking in Indonesia, as it encompasses the COVID-19 pandemic and the subsequent recovery period, which significantly altered financing behavior, liquidity management, and competitive dynamics within the banking industry. During this period, Islamic banking experienced substantial acceleration in asset growth, financing expansion, and the accumulation of Third-Party Funds. However, despite this progress, the market share of Islamic banks remains considerably smaller than that of conventional banks, raising concerns regarding the effectiveness of internal performance indicators in strengthening industry competitiveness under both crisis and post-crisis conditions. This study examines the influence of the Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (OEOI/BOPO), and Third-Party Funds on the market share of Islamic Commercial Banks in Indonesia during 2019–2024. A quantitative research design was employed using secondary panel data obtained from the annual financial statements of Islamic Commercial Banks and official publications issued by the Otoritas Jasa Keuangan (OJK). Panel data regression was applied as the analytical method, with model selection conducted through the Chow and Hausman Tests, both of which indicate that the Fixed Effects Model (FEM) is the most appropriate estimation approach. The empirical results reveal that FDR has a significant negative effect on market share, indicating that an expansion in financing does not necessarily strengthen market position when it is not supported by adequate asset quality and effective risk governance, particularly during periods of economic instability. In contrast, OEOI/BOPO does not exhibit a significant effect, suggesting that variations in operational efficiency have not yet become a decisive factor in shaping the market share of Islamic Commercial Banks. Meanwhile, Third-Party Funds demonstrate a positive and significant effect, underscoring the central role of fund mobilization capacity in expanding market presence and reinforcing competitive positioning. Overall, the findings suggest that strategies to enhance the market share of Islamic Commercial Banks in the post-pandemic period should prioritize strengthening fund mobilization and improving financing quality, while maintaining prudent liquidity management and consistent operational stability.